1999
DOI: 10.1111/j.1600-0609.1999.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

2‐Chlorodeoxyadenosine (cladribine) in the treatment of hairy cell leukemia and hairy cell leukemia variant: 7‐year experience in Poland

Abstract: Between January 1991 and December 1997, 103 patients, 97 with typical hairy cell leukemia (HCL) and 6 with HCL‐variant (HCL‐V) were treated with 2‐chlorodeoxyadenosine (2‐CdA) given as 2‐h infusion for 5 consecutive d at a daily dose 0.12 mg/kg. To our knowledge this is the largest cohort of HCL patients treated with this type of regimen. Median follow‐up amounted to 36 months. Fifty‐six of 97 patients with typical HCL were newly diagnosed and 41 were relapsed after previous treatment. Splenectomy as a first‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 37 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…Although the case number is relatively small, our experience suggests splenic irradiation should not be considered as the frontline treatment when other options are feasible. With regard to alternative treatment, HCL-V was reported to have partial response to purine nucleoside analog in less than half of patients [2,27,28,29]. Our experience of purine nucleoside analog for the treatment of HCL-V was limited.…”
Section: Discussionmentioning
confidence: 95%
“…Although the case number is relatively small, our experience suggests splenic irradiation should not be considered as the frontline treatment when other options are feasible. With regard to alternative treatment, HCL-V was reported to have partial response to purine nucleoside analog in less than half of patients [2,27,28,29]. Our experience of purine nucleoside analog for the treatment of HCL-V was limited.…”
Section: Discussionmentioning
confidence: 95%
“…Cladribine is today considered the therapy of choice in HCL [15]. Five patients received Cladribine, as soon as they were diagnosed.…”
Section: Immunophenotypementioning
confidence: 99%
“…In chemotherapy-naive HCL, one course of 2-CdA induces complete response (CR) and long-term survival in the vast majority of patients. [1][2][3][4][5] Given this considerable clinical efficacy, the major challenge regarding 2-CdA therapy is reduction of side effects, especially severe infections that may lead to septic death. Lauria et al 6 suggested that a novel schedule based on 6 weekly 2-hour 2-CdA infusions could be as effective as the standard 7-day and 5-day protocols but associated with less neutropenia and fewer life-threatening infections.…”
Section: Introductionmentioning
confidence: 99%